The rough guide to San Francisco : with the entire bay area, including wine country. - Edwards, Nick, ....-; Ellwood, Mark, ....- ([S.l.] : Rough Guides, 2003)
Arguably the most beautiful city in the U.S. and self-proclaimed as the most liberal, San Francisco provides a wide variety of sights, activities, and outings. This guide covers them all, from the student haunts of Berkeley to the vineyards of the Napa and Sonoma valleys to the natural beauty of Marin County. of color maps. of color photos.